Exploring the Determinants of Digital Content Adoption By Academics: The Moderating Role of Environmental Concerns and Price Value. (June 2020) - Hidayat-ur-Rehman, Imdadullah; Akram, Muhammad Shakaib; Malik, Aneela; Mokhtar, Shamsul A.; Bhatti, Zeeshan Ahmed; Khan, Muhammad Asif
The study investigates the underlying motives facilitating users' continuance intention for digital content in academic settings. Extending the expectation confirmation model of IS continuance (ECM-ISC), the study proposes a conceptual model by incorporating personal and technological antecedents of users' continuance intention for digital content. In addition, users' environmental concerns and price value are considered as potential moderators in the relationship between their satisfaction and continuance intention for digital content. An online survey was used to collect data from 311 digital content users of a large public university in Saudi Arabia. Structural equation modeling was used to test the relationships in the conceptual model. The results obtained from SmartPLS 3.2 confirm that compatibility, convenience, self-efficacy, and facilitating conditions are the predictors of confirmation and usefulness of digital content. The confirmation of expectations and perceived usefulness result in greater satisfaction with the digital content, which in turn leads to users' continuance intention. In addition, the article provides empirical evidence for the impact of environmental concerns on the satisfaction–continuance intention relationship, thus opening a novel research debate. The study is expected to offer new insights both for academicians and managers of digital content.